2006
DOI: 10.1111/j.1556-4029.2006.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Dog Maulings Associated With Infant Swings

Abstract: We present three cases of fatal dog maulings of infants placed in mobile infant swings, a phenomenon not previously described in the literature. In each case, the victim was left in a mobile swing, unsupervised by an adult, and the attacking dog was a family pet. Case 1 involved an 18-day-old male infant attacked by a pit bull; Case 2 involved a 3-month-old male infant attacked by a Chow Chow and/or a Dachshund, and Case 3 involved an 18-day-old female infant attacked by a Labrador-pit bull mix. These cases no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
2
19
0
7
Order By: Relevance
“…17 In a study 18 of dog-child communication, children between 2 and 5 years old took the initiative in interacting with body contact with a pet dog, and younger children tended to be more aggressive in their interactions. 17 In a study 18 of dog-child communication, children between 2 and 5 years old took the initiative in interacting with body contact with a pet dog, and younger children tended to be more aggressive in their interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In a study 18 of dog-child communication, children between 2 and 5 years old took the initiative in interacting with body contact with a pet dog, and younger children tended to be more aggressive in their interactions. 17 In a study 18 of dog-child communication, children between 2 and 5 years old took the initiative in interacting with body contact with a pet dog, and younger children tended to be more aggressive in their interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that younger children are more frequently bitten on the face, head, or neck, by the family dog, and in their own homes. However, fatal attacks of infants are most often inflicted by pet dogs in the infant' s home, 17,20 and infants are no less vulnerable when asleep than when awake. 20 However, there appeared to be a lack of awareness of this risk among dog owners in the present study, in that 24% of respondents disagreed with the statement "dogs should never be left alone with infants."…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published literature on animal scavenging in a forensic context is case based [4][5][6][7] with only a few experimentally based studies reported [8,9]. In the ecological setting there have been many published papers on scavenging and surveys of scavenging guilds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[5] Another recent case study of three fatal dog attacks in Baltimore found that in each instance an infant was left unsupervised in a mobile swing at the time of the attack by a family dog. [9]…”
Section: Introductionmentioning
confidence: 99%